Tracheal injury characterized by subcutaneous emphysema and dyspnea after improper placement of a Sengstaken–Blakemore tube: A case report. Issue 30 (July 2018) - Wang, Hui-shan; Lin, Jie; Wang, Fei; Miao, Lin
Abstract: Rationale: Tracheal injury characterized by subcutaneous emphysema and dyspnea can occur following the use of a Sengstaken–Blakemore tube. Should tracheal injury occur, it may be possible to manage resultant airway obstruction with a tracheal stent. Patient concerns: We describe the case of a 51-year-old patient who developed a tracheal injury when a Sengstaken–Blakemore tube was inadvertently inserted into the patient's trachea. Diagnoses: Liver cirrhosis, gastric-fundus variceal bleeding, tracheal injury. Interventions: Polyglycol and tissue glue were injected intravenously, and endoscopic variceal ligation was performed. A Sengstaken–Blakemore tube was used to stop the bleeding. A covered tracheal stent was placed via fiberoptic bronchoscopy to relieve the tracheal injury due to improper placement of a Sengstaken–Blakemore tube. Outcomes: After placement of the tracheal stent, the patient was able to breathe spontaneously and subsequently recovered. Lessons: Some precautions must be taken to avoid placing a Sengstaken–Blakemore tube in the trachea. If a tracheal injury occurs following misplacement of a Sengstaken–Blakemore tube, it may be possible to manage resultant airway obstruction by placing a tracheal stent. Abstract : Supplemental Digital Content is available in the text